TYPES OF ASSESSMENT IN FOREIGN LANGUAGE TEACHING - Davronova Shahlo (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Assessment plays a central role in foreign language teaching because it provides learners’ progress, teachers’ instructional effectiveness and curriculum quality. This article examines the main types of assessments used in foreign language teaching, including formative, summative, diagnostic, placement, teachers, and alternative assessment. The study also discusses how these assessment types contribute to language development and learner motivation. The analysis based on established theories of language assessment and current pedagogical practices. The findings show that balanced use of different assessment types leads to more effective and learner-centered language instruction.